Condensation of Ded1p promotes a translational switch from housekeeping to stress protein production - Iserman, Christiane; Desroches Altamirano, Christine; Jegers, Ceciel; Friedrich, Ulrike A.; Zarin, Taraneh; Fritsch, Anatol W.; Mittasch, Matthäus; Domingues, Antonio; Hersemann, Lena; Jahnel, Marcus; Richter, Doris; Guenther, Ulf-Peter; et al. (Cell, 2020)
Cells sense elevated temperatures and mount an adaptive heat shock response that involves changes in gene expression, but the underlying mechanisms, particularly on the level of translation, remain unknown. Here we report that, in budding yeast, the essential translation initiation factor Ded1p undergoes heat-induced phase separation into gel-like condensates. Using ribosome profiling and an in vitro translation assay, we reveal that condensate formation inactivates Ded1p and represses translation of housekeeping mRNAs while promoting translation of stress mRNAs. Testing a variant of Ded1p with altered phase behavior as well as Ded1p homologs from diverse species, we demonstrate that Ded1p condensation is adaptive and fine-tuned to the maximum growth temperature of the respective organism. We conclude that Ded1p condensation is an integral part of an extended heat shock response that selectively represses translation of housekeeping mRNAs to promote survival under conditions of severe heat stress.